Actitudes y prácticas contra cáncer de cuello uterino y mama en adolescentes de un colegio público de Trujillo - Cáceda Ñazco, Giovanna Sara (2019)
The objective of this research was to determine the level of attitudes and practices against cervical cancer and breast cancer in teenagers of the Modelo Trujillo school, 2016. The sample consisted of 165 students from the fifth year of secondary, who in 2012 participated in the educational program: More neurons than hormones against cancer of the cervix and breast. From the perspective of health promotion, sexual abstinence, delayed initiation of sexual intercourse and breast self-examination were promoted. After 4 years, the level of attitudes against cervical cancer and breast cancer, shows that 3.0% of adolescents have a regular level of attitudes, 97.0% of adolescents have a good attitude level, and no adolescent has a level of bad attitude, 2.4% of adolescents have a regular level of practices, in relation to practices against cervical and breast cancer, 97.6% of adolescents have a good level of practices and no adolescent presents bad practice level. In relation to attitudes and practices against cervical cancer and breast cancer 1.8% of adolescents have a regular level of attitudes and a level of regular practices and 96.4% of adolescents have a good level of attitudes and a level of practices also good A chi-square value of 72,300 is observed with probability 0.000 being highly significant, having a relationship between variables.